2014
DOI: 10.5935/0946-5448.20140002
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ultrasound-computer-craniocorpography in different vestibular disorders

Abstract: Ultrasound-computer-craniocorpography is a useful method in the examination of the balance system disorders. The differential diagnostic value is not sufficient alone, we needs other investigations for the topical diagnosis of the vestibular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…However, in another study, it increased in patients with peripheral system disease. [13] Our study revealed that this value was affected by anthropometric data. There was a statistically significant negative correlation between self-spin value and head length.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, in another study, it increased in patients with peripheral system disease. [13] Our study revealed that this value was affected by anthropometric data. There was a statistically significant negative correlation between self-spin value and head length.…”
Section: Discussionmentioning
confidence: 66%
“…The data obtained from our study was fitting to normal range values. Szirmai et al [13] found that the longitudinal deviation increased in patients with vestibular system pathology. In our study, we determined a significantly moderate negative correlation between this parameter and neck circumference, and showed that the self-spin value was not affected by vestibular system pathology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Az eredményeket részben grafikusan, radarképen, részben numerikusan jeleníti meg a ZEBRIS CMS® szoftver. A Romberg-próba négy paraméterét: a longitudinális és a laterális elmozdulást, a mozgás alapterületét és az elmozdulás szögét értékeltük [14]. Az Unterberger-Fukuda-próba során (a beteg csukott szemmel helyben jár) a longitudinális és a laterális elmozdulást, a szög elfordulást (anguláris deviáció) és a test önmaga kö-rüli elfordulását vizsgáltuk (self-spin).…”
Section: áBra)unclassified
“…Using ultrasound markers on head and shoulders, the computer measures and analyzes the numerical data of vestibulospinal tests of the patients suffering from vertigo and/or balance disorders [10]. The main parameters for evaluating the standing test are the longitudinal and lateral sway in cm, the torticollis angle in degrees, and the forehead covering area in cm 2 .…”
Section: Methodsmentioning
confidence: 99%